DRUG UTILIZATION PATTERNS IN OUTPATIENTS WITH OSTEOARTHRITIS AT THONG NHAT HOSPITAL VIETNAM FROM 2016 TO 2024 - Nguyên, Trần Thị Hồng; Bảo, Nguyễn Hữu Thiên; Nguyệt, Quang Ánh; Nga, Nguyễn Thị Quỳnh; Mai, Trần Thị Phương; Hiền, Phạm Thị Thu; Nga, Đặng Thị Kiều (Journal of Health and Aging, 2026)
Osteoarthritis is a chronic musculoskeletal disorder characterized by pain, functional impairment, and diminished quality of life, with knee, hip, and hand osteoarthritis representing the most prevalent clinical manifestations. This study aimed to analyze patient characteristics and patterns of medication utilization in the outpatient management of osteoarthritis at Thong Nhat Hospital during the period from 2016 to 2024. A retrospective cross-sectional study was conducted involving 40,916 patients diagnosed with osteoarthritis based on ICD-10 codes M16, M17, and M18. The results indicated that knee osteoarthritis accounted for most cases (97.28%). The mean age of patients was 59 years, with most patients belonging to the 30–65 and ≥65 age groups. A high prevalence of comorbid conditions was observed, particularly cardiovascular diseases and metabolic disorders. Oral NSAIDs were the most frequently prescribed medications (66.2%), followed by analgesics and topical NSAIDs. Co-prescription network analysis demonstrated that oral NSAIDs occupied a central position in most medication combination patterns, especially among patients with knee osteoarthritis, who exhibited a higher degree of polypharmacy compared with patients with osteoarthritis affecting other joint sites. These findings provide evidence to support individualized treatment strategies and to improve the effectiveness of osteoarthritis management in the Vietnamese clinical context.